THE URBANITY CONSICOUS OF YOUTH IN TURKEY FROM TRADITIONAL NOMADISM TO MODERN NOMADISM - AN ANALYSIS ON THE CASE OF KIRIKKALE (Third Sector Social Economic Review, 2016)
When its historical background was analysed, Turkish tradition is observed to be composed of a production of a society living a nomadic life. Although lived a nomadic life, Turkish society achieved to found great and settled empires with the help of its cultural life practices, too. When the geographical locations of these empires were examined, it is observed that these empires were founded in different geographical locations, became dominant in this area, and this places were sanctified and described as a fatherland by Turkish society. In this context, the nomadic life, which is in cultural codes of Turkish society, shouldn’t be evaluated as not adhering to a certain piece of land. Traditional nomadism means a fatherland-seeking instead of rootlessness when compared to other nomadic tribes. Turkish people are apt on evaluating the place where they migrated as a fatherland. To determine the effect of this situation that continues from the past to the modern societies to urbanity conscious is very important for city policies today. In thiscontext, it is very important to identify the urbanity conscious of youth in Kırıkkale founded as a product of industrialization process in termsof identifying the effect of traditional nomadism on urbanity conscious. In this study, within the context of the project “The Place of Kırıkkale for the Future Planning of Youth in Kırıkkale in the Context of Urbanity Conscious” numbered 2014/046 supported by Kırıkkale University BAP unit, the data and findings will be used, and the urbanity conscious of youth in Kırıkkale, revealed in the project, will be correlated with cultural codes and explained. The analyses are important in terms of cultural codes, urbanity, fatherland, appropriation and determination of the factors affecting these. From the analyses it was revealed that cultural codes were effective to the factors like urbanity, homeland and civic ownage, and it was concluded that the reason for not having a proper urban consciousness arose from not meeting the needs and expectations of young people in the city.
Keywords: Traditional Nomadism; Fatherland; City; Urbanity Conscious; Kırıkkale; Turkish Culture